PENGGUNAAN NOTASI BALOK DALAM KEGIATAN ESTRAKURIKULER PADUAN SUARA DI SMA NEGERI 8 PADANG - Nando Iqrak Tolanda; Yensharti Yensharti; Esy Maestro (SENDRATASIK UNP, 2018)
This article aims to describe the use of beam notation in choir extracurricular activities at SMA Negeri 8 Padang. This type of research was a qualitative research with a descriptive approach. Data were collected through literature studies, interviews and observation and training. The instruments of this research were the researcher himself with the help of other instruments such as notebooks and stationery, photo / cell phone cameras and song scores. This research was begun with the design, implementation, evaluation, and provided materials on beam notation and choirs as well as material on vocal techniques such as breathing exercises, intonation, and articulation to students in accordance with this study.The results of the study found that choir extracurricular activities at SMA Negeri 8 Padang had been going well. It was evidenced by the ability of participants to read rang talui song by using beam notation in the basic tone of D major. Students also have been able to read rang talu songs according to the type of sound that has been shared, namely soprano and alto in the basic tone of D major. Therefore, the activities implemented in this study have achieved good success rates. Keywords: the use of notation beams, extracurricular choral